Dental ergonomics among dental students of a teaching hospital in the Koshi Province: a questionnaire survey - Kumar, Abhishek; Kattel, Bibek; Rijal, Bipul; Shrestha, Ashish; Bhagat, Tarakant; Agrawal, Santosh Kumari (International Journal Of Community Medicine And Public Health, 2025)
Background: The present study was conducted to assess knowledge, attitude, and practice of dental ergonomics among dental undergraduates (UGs), interns, and postgraduate students (PGs) in a teaching hospital in the Koshi province. Methods: A cross-sectional questionnaire-based study was conducted in a tertiary care center. The questionnaire was distributed to 228 dental students to assess their knowledge, attitude, and practice related to dental ergonomics. The responses obtained were presented in terms of frequency and percentage. Results: In the surveyed population, 211 (92.54%) students were aware of musculoskeletal disorders related to dental practice, while 175 (76.75%) students knew about dental ergonomics. The study highlights a notable prevalence (77 students; 33.8%) of musculoskeletal disorders (MSDs) among dental students, which they believed were related to their profession. Regarding habits, 144 (63.16%) students practiced both sitting and standing dentistry, while 83 (36.40%) students performed only sitting dentistry. Only 59 (25.88%) participants practiced 4-handed dentistry and 88 (52.07%) students of those who did not practice it swiveled to better access the area. The majority, 217 (95.18%) students, suggested integrating dental ergonomics into their academic curriculum, while 212 (93%) students expressed interest in participating in workshops focused on dental ergonomics. Conclusions: The study highlights the awareness among dental students about musculoskeletal disorders and dental ergonomics. However, the notable prevalence of musculoskeletal disorders during dental practice emphasizes the importance of addressing ergonomic practices within the profession and the importance of incorporating dental ergonomics into the academic curriculum.